A novel technique to identify AIS transmissions from vessels which attempt to obscure their position by switching their AIS transponder from normal transmit power mode to low transmit power mode. (15th September 2022) - Kelly, Peter
Abstract: Automatic Identification Systems (AIS) are transponder systems installed on marine vessels which transmit the location, speed and other vessel details. These signals are received by shore side AIS Base stations. The use of AIS is mandatory under international SOLAS regulations for certain categories of vessels. AIS is used to monitor for pollution, search and rescue (SAR) and illegal fishing activity. Some vessel operators deliberately interfere with their AIS transponders, including spoofing their real position or switching their AIS transponder to low transmit power, to reduce the likelihood of being detected but still being in compliance with SOLAS regulations. This might suggest that they are involved in nefarious activity. This paper presents a technique to detect vessels which are switching their Class-A, AIS transponders from normal transmit power to low transmit power mode, by utilising the Received Signal strength Indicator field (RSSI) that the receiving Base Station tags incoming AIS messages with. The technique presented, analyses received RSSI in combination with predicted RSSI values via mathematical modelling and presents a unique detection algorithm. Data from the Irish National AIS was used for the study. Although only a small amount of testing was carried out, results showed that for a test vessel which switched its transponder to low power transmit mode, it was found that a specific drop in RSSI of approximately 10 dBm (decibel-milliwatts) was detectable for different distances from the receiving base station.